The Effects of the Natural Components on the Ageing of the Italian Population - Sacco, Giuseppina; Sacco, Pietro (European Scientific Journal, ESJ, 2018)
The most remarkable demographic changes that have been happening in our society, and causing considerable social effects, are the significant decrease of fecundity and the increase of average life expectancy at birth. The combined effect of these factors causes the ageing of population, thus representing the theoretical basis of the phenomenon under study in this essay. We will analyse the evolution of fecundity in Italy and in Italian single regions , thus highlighting the change of its intensity over the years. Moreover, we will focus on the analysis of average life expectancy at birth by verifying both its time trend and how it changes because of the variations of mortality by age. Thanks to a suitable method, detailed data of ISTAT and EUROSTAT will be used to show the interesting findings of the fecundity geography and variations of mortality by age. Nowadays, compared to just over twenty years ago, we have been characterized a reversal of the fecundity geography. Furthermore, a new increase of life expectancy at birth a further increase has been achieved.